Functional Food Innovation of Moringa Oleifera L. Seed-Based Plant Yogurt: Fermentation Optimization with Three Lactic Acid Bacteria - Anak Agung Ngurah Dwi Ariesta Wijaya Putra; Putu Rima Sintyadewi (Jurnal Pijar MIPA, 2026)
Moringa (Moringa oleifera L.) is a nutrient-dense plant with significant potential as a functional food source. Beyond its widely utilized leaves, moringa seeds possess substantial potential due to their high protein and bioactive compound content; however, their current utilization remains limited. This study aimed to evaluate the effect of varying inoculum proportions of three Lactic Acid Bacteria (LAB) species on the characteristics of moringa seed-based plant-based yogurt. The research followed a Completely Randomized Design (CRD), employing various inoculum proportions of Lactobacillus bulgaricus, Streptococcus thermophilus, and Lactobacillus plantarum. Data were statistically analyzed using ANOVA followed by Duncan’s Multiple Range Test (DMRT) at a 95% confidence level. The results indicated that varying inoculum proportions significantly affected the total LAB count, total soluble solids, total acidity, viscosity, pH, proximate composition, and antioxidant activity. The formulation with a 1%:2%:2% ratio (P7) produced moringa seed yogurt with the optimal functional characteristics and consumer acceptance. This study concludes that the synergy among the three LAB species effectively optimizes the quality of moringa seed-based plant-based yogurt. This product has potential as a functional food alternative for individuals with lactose intolerance, while contributing to food security by downstreaming nutrient-rich local commodities.